Diamond research: highlights from 2023 - Editors, Functional Diamond (Functional Diamond, 2024)
The year 2023 stands as a pivotal chapter in the chronicles of diamond research, marked by a series of exciting progress that have illuminated the multifaceted potential of this extraordinary material. The editors of Functional Diamond selected some key research achievements of 2023, including electronics, quantum science, MEMS, heat dissipation, electrochemistry, diamond growth, and optics. As we navigate through the highlights encapsulated in this retrospective, it becomes evident that the research progress has not only broadened the horizons of scientific understanding but has also laid the foundation for unprecedented possibilities in diverse fields.